Deoxypyridinoline level in gingival crevicular fluid as alveolar bone loss biomarker in periodontal disease - Agustin Wulan Suci Dharmayanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Periodontal diseases have high prevalence in Indonesia. They are caused by bacteria plaque that induced host response to release pro inflammatory mediator. Pro inflammatory mediators and bacteria product cause degradation of collagen fibers in periodontal tissue. Deoxypyridinoline is one of pyridinoline cross-link of collagen type I that can be used as biomarker in bone metabolic diseases, however, their contribution to detect alveolar bone loss in periodontal diseases remains unclear. Purpose: This study was to evaluate deoxypyridinoline level in gingival crevicular fluid as alveolar bone loss biomarker on periodontal disease. Methods: This study used 24 subjects with periodontal diseases and 6 healthy subjects. Dividing of periodontal disease was based on index periodontal. Gingival crevicular fluid was taken at mesial site of maxillary posterior tooth by paper point and deoxypyridinoline be measured by ELISA technique. Results: We found increasing of deoxypyridinoline level following of the severity of periodontal diseases. There was also significant difference between healthy subjects and periodontal diseases subjects (p<0.05). Conclusion: Deoxypyridinoline level in gingiva crevicular fluid can be used as alveolar bone loss biomarker in periodontal disease subjects.Latar belakang: Prevalensi penyakit periodontal di Indonesia cukup tinggi. Ini disebabkan oleh bakteri plak yang merangsang respon tubuh untuk mengeluarkan mediator keradangan. Mediator keradangan dan produk bakteri menyebabkan degradasi serat kolagen jaringan periodontal. Deoksipiridinolin merupakan salah satu ikatan piridinium dari kolagen tipe I yang dapat digunakan sebagai biomarker penyakit metabolisme tubuh. Akan tetapi, penggunaan deoksipiridinolin untuk mendeteksi kehilangan tulang alveolar pada penyakit periodontal masih belum jelas. Tujuan: Tujuan penelitian ini untuk mengetahui bahwa kadar deoksipiridinolin pada cairan krevikular gingival dapat digunakan sebagai biomarker kehilangan tulang alveolar pada penyakit periodontal. Metode: Penelitian ini menggunakan 24 subyek penelitian yaitu 24 orang dengan penyakit periodontal dan 6 orang tidak menderita penyakit periodontal. Pembagian penyakit periodontal berdasarkan indeks periodontal. Cairan krevikular gingival diambil dari bagian mesial gigi posterior atas dengan menggunakan paper point dan diukur kadar deoksipiridinolin dengan menggunakan teknik ELISA. Hasil: Hasil penelitian menunjukkan ada peningkatan kadar deoksipiridinolin seiring dengan tingkat keparahan penyakit periodontal. Hasil statistik juga menunjukkan ada perbedaan rata-rata antara subyek penelitian yang tidak menderita penyakit dengan subyek yang menderita penyakit periodontal (p<0,05). Kesimpulan: Kadar deoksipiridinolin pada cairan krevikular gingival dapat digunakan sebagai biomarker kehilangan tulang alveolar pada penderita penyakit periodontal.